Label-free plasmonic biosensors for point-of-care diagnostics: a review. (2nd January 2019) - Soler, Maria; Huertas, Cesar S.; Lechuga, Laura M.
ABSTRACT: Introduction : Optical biosensors, particularly those based on nanoplasmonics technology, have emerged in recent decades as a potential solution for disease diagnostics and therapy follow-up at the point-of-care (POC). These biosensor platforms could overcome some of the challenges faced in conventional diagnosis techniques offering label-free assays with immediate results and employing small and user-friendly devices. Areas covered : In this review, we will provide a critical overview of the recent advances in the development of nanoplasmonic biosensors for the POC diagnostics. We focus on those systems with demonstrated capabilities for integration in portable platforms, highlighting some of the most relevant diagnostics applications targeting proteins, nucleic acids, and cells as disease biomarkers. Expert commentary : Despite the attractive features of label-free nanoplasmonic sensors in terms of miniaturization and analytical robustness, the route toward an effective clinical implementation involves the integration of fully automated microfluidic systems for sample processing and analysis, and the optimization of surface biofunctionalization procedures. Additionally, the development of multiplexed sensors for high-throughput analysis and including specific neoantigens and novel biomarkers in detection panels will provide the means for delivering a powerful analytical technology for an accurate and improved medical diagnosis.